Elastic recoil detection analysis (ERDA) in hydrogenated samples for TNSA laser irradiation. (19th November 2015) - Torrisi, Lorenzo; Cutroneo, Mariapompea
Abstract : This paper provides an overview of theory, method, and examples concerning the elastic recoil detection analysis employed in forward recoil spectrometry to monitor the hydrogen content of hydrogenated targets prepared to be irradiated by high‐intensity lasers in target normal sheath acceleration regime. Polymers, semiconductors, and 'advanced foils' were analyzed to evaluate their hydrogen content as potential source for plasma proton acceleration. Helium ions at 2.0 MeV were employed as a target probe in a glancing angle to induce recoil hydrogen atoms and to measure the hydrogen concentration in the first superficial layers of the target. Results demonstrated that the hydrogen degassing occurs under ion beam irradiation, that its content depends on the polymer specie and porosity, that it is possible to control thin hydrogenated film thickness, and that the technique has sufficient isotope resolution to separate hydrogen from deuterium content. Copyright © 2015 John Wiley & Sons, Ltd.